Brain cortical characteristics of skilled sensorimotor performance - Mierau, A.; Hannemann, M.; Hülsdünker, T.; Karamanidis, K.; Sueptitz, F.; Mierau, J.; Strüder, H. K. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Athletes can achieve striking sensorimotor skills after years of extensive training. So far, only little is known about the neural mechanisms underlying such skilled performance. Recent electroencephalographic (EEG) studies compared athletes with non-athletes and/or high with low performance within a sample of subjects. These studies showed that activity in the alpha (7-12 Hz) and beta (13-30 Hz) frequency band (e.g. Del Percio et al. 2009) as well as frontal midline theta (4-7 Hz) band activity (e.g. Doppelmayr et al. 2008) are related to attention based sensorimotor performance. However, the available literature provides strong evidence that motor behavior is characterized not only by changes in alpha and beta but particularly in gamma band activity. Moreover, it has been shown that during motor behavior the topographical patterns of gamma compared with alpha and beta band activity were more discrete, somatotopically more specific and more consistent with the traditional maps of sensorimotor functional anatomy (Crone et al. 1998) Therefore, the present study should extend previous research by further considering the power in the gamma-1 (30-35 Hz) and gamma-2 (35-40 Hz) bands over the primary motor cortex contralateral to the aiming arm/hand during air pistol shooting in experts and novices for high and low scores, respectively. As compared to novices, experts showed significantly higher shooting scores and significantly less anterior-posterior fluctuations of the center of pressure immediately prior to the shot. Both, gamma-1 and gamma-2 power were significantly lower in experts compared to novices 3 sec prior to the shot. Furthermore, gamma-2 power was significantly lower in high compared to low scores 1 sec prior to the shot. Our findings suggest that gamma oscillations over the primary motor cortex are related to sensorimotor performance. Higher gamma power values in novices as well as in low score shots may reflect increased compensatory motion of the aiming arm/hand as a result of reduced dynamic stability.